Family treatment court participation and permanency in a rural setting: Outcomes from a rigorous quasi‐experiment. Issue 4 (1st March 2021) - Lloyd Sieger, Margaret H.; Becker, Jessica; Brook, Jody
Abstract: Substance‐affected families are frequently cited as the most challenging families to serve within the child welfare context, particularly in rural settings where treatment services may be few and far between. Growing evidence suggests that family treatment courts (FTCs) may be more effective than their traditional counterpart at achieving key child welfare goals; however, prior studies have been limited in their methodological rigour. This study used treatment and matched comparison data to test foster care exit patterns of families with children in foster care due to parental substance use. Treatment group data were collected on a sample of 91 children with open dependency cases in an integrated FTC in a rural Midwestern town. Propensity score nearest neighbour one‐to‐two matching was used to identify a comparison group of 146 children. Findings suggest that FTC participation significantly influenced foster care exits. Survival analyses revealed that FTC children were 170% more likely to reunify, and 58% more likely to achieve permanency, than comparison cases. The effect of FTC participation on likelihood of reunification and likelihood of permanency was stronger when models estimated outcomes from FTC start date, rather than child removal date. Implications for social work practice, research, and education are discussed.